1993
DOI: 10.1038/bjc.1993.208
|View full text |Cite
|
Sign up to set email alerts
|

The use of tumour markers CEA, CA-195 and CA-242 in evaluating the response to chemotherapy in patients with advanced colorectal cancer

Abstract: Summary Tumour markers CEA, were measured in 33 patients undergoing chemotherapy for advanced colorectal cancer. The aim was to determine whether they could be used to accurately monitor the course of the disease, and reduce the need for imaging. Treatment with a 5-fluorouracil based regimen resulted in a partial response in nine patients (27%), whereas the remainder either had disease stabilisation or suffered from progression. Before treatment the CEA was elevated in 85% of patients and the and CA-242 in 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
41
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 10 publications
5
41
0
1
Order By: Relevance
“…Tumour antigen levels have been used for many years in the clinical management of cancer (Goldenberg et al, 1981). They have proved of value in detecting recurrent disease (NIH Consensus Statement, 1981;Hida et al, 1996), monitoring the effects of chemotherapy and predicting prolonged survival (Hine and Dykes, 1984;AllenMersh et al, 1987;Ward et al, 1993). A combined analysis of marimastat clinical trials, in patients with carcinoma of the pancreas, ovary, colon and prostate, has demonstrated a dose-dependent reduction in the rate of rise of cancer antigens (Nemunaitis et al, 1998).…”
mentioning
confidence: 99%
“…Tumour antigen levels have been used for many years in the clinical management of cancer (Goldenberg et al, 1981). They have proved of value in detecting recurrent disease (NIH Consensus Statement, 1981;Hida et al, 1996), monitoring the effects of chemotherapy and predicting prolonged survival (Hine and Dykes, 1984;AllenMersh et al, 1987;Ward et al, 1993). A combined analysis of marimastat clinical trials, in patients with carcinoma of the pancreas, ovary, colon and prostate, has demonstrated a dose-dependent reduction in the rate of rise of cancer antigens (Nemunaitis et al, 1998).…”
mentioning
confidence: 99%
“…Evaluation by this means is, however, expensive and time-consuming for the patient. A simple and inexpensive method to monitor response would be the repeated measurement of tumour markers such as carcinoembyronic antigen (CEA), CA 19-9 or , which are commonly elevated in patients with gastrointestinal cancer (Martin et al, 1976;Safi et al, 1978;Kornek et al, 1992;Ward et al, 1993). It is recognised, however, that these markers do not always accurately reflect the course of the disease.…”
mentioning
confidence: 99%
“…It is recognised, however, that these markers do not always accurately reflect the course of the disease. The limitations to their use in isolation is the overestimation of the number of patients who respond to treatment and, more seriously, underestimation of the number suffering progressive disease as demonstrated on CT (Allen-Mersh et al, 1986;Ward et al, 1993).…”
mentioning
confidence: 99%
“…The recent studies of showed that it has a higher sensitivity than CA-50 in primary colorectal cancer and a low false positivity in benign liver disease (Kuusela et al, 1991;Nilsson et al, 1992). In prinary colorectal cancer, additional use of CA-242 improves the diagnostic sensitivity of CEA alone (though it still remains limited) (Roberts et al, 1992), and CA-242 has also been shown to compklment CEA monitoring of patients reiing chemotherapy for liver metasta from colorectal cancer (Ward et al, 1993 …”
mentioning
confidence: 99%